ANALISIS PUTUSAN NOMOR 559/PID.B/2017/PN.BYW. PENGADILAN NEGERI BANYUWANGI TENTANG PENYEBARAN AJARAN KOMUNISME/MARXISME-LENINISME SECARA MELAWAN HUKUM BERDASARKAN PASAL 107A KUHP - Andreas Purba; Firman Wijaya (Jurnal Hukum Adigama, 2019)
Budi Pego was charged with violating Article 107a of Law Number 27 of 1999 concerning Amendment to the Criminal Law Code relating to crimes against State security, because of. Because of these accusations, Budi Pego was charged with a 10-month prison sentence in the Banyuwangi District Court. The problem faced is how criminal liability on the perpetrators of the spread of the teachings of communism in terms of Article 107A of the Criminal Code (case study of decision No. 559 / Pid.B / 2017 / PN.Byw)? The research method used is normative legal research. The results showed that criminal liability on the perpetrators of the spread of the teachings of communism in terms of Article 107A of the Criminal Code in Decision No. 559 / Pid.B / 2017 / PN.Byw. it is inappropriate if this criminal liability model is applied to criminal liability to individuals. Considering that individual accountability still requires actions and mistakes as a basic element of accountability. That is, without any deeds and mistakes, there is no criminal liability. Regarding the Budi Pego case, the policy of criminalizing the ideology of Communism/Marxism-Leninism was decriminalized. If this cannot be done, then the legislators need to revise Law No. 27 of 1999 with the concept of eliminating articles containing formal offenses and replacing them with the formulation of material offenses and in the formulation of the weight of sanctions.